PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP TAX AVOIDANCE DENGAN KUALITAS AUDIT SEBAGAI PEMODERASI (Studi Empiris Terhadap Perusahaan Subsektor Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia 2020-2024) - Risaly Claudia Sidabutar; Nur Cahyonowati (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of profitability and leverage on tax avoidance with audit quality as a moderating variable. Tax avoidance is proxied by the Effective Tax Rate, profitability is measured using Return on Assets, leverage is measured using the Debt to Equity Ratio, while audit quality is measured using a dummy variable based on the affiliation of Public Accounting Firms with Big Four and Non-Big Four firms. This study also uses institutional ownership, sales growth, and firm size as control variables.This study employs a quantitative approach using secondary data from food and beverage subsector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The sample was selected using the purposive sampling method, resulting in 155 observations. The analytical method used is panel data regression with Moderated Regression Analysis. The model selection results indicate that the Random Effect Model is the most appropriate model for this study.The results show that profitability has a significant positive effect on tax avoidance, while leverage has a significant negative effect on tax avoidance. However, audit quality is unable to moderate the effect of profitability or leverage on tax avoidance. These findings indicate that audit quality is not sufficiently strong in limiting companies’ tendency to engage in tax avoidance, particularly among food and beverage subsector companies during the research period.